Social Media Use, Digital Literacy, and Counseling Effectiveness as Predictors of Reproductive Health Knowledge among Medical Students: An Educational Management Perspective - Inggrid C Mahama; Deitje A. Katuuk; Ruth Umbase; Henny Nikolin Tambingon (JR Education, 2026)
This article analyzes the influence of social media use, digital literacy, and the effectiveness of reproductive health counseling on medical students' reproductive health knowledge. The study is positioned within educational management because digital platforms, information literacy, and counseling programs are not merely instructional tools; they represent a managed learning ecosystem that requires planning, implementation, monitoring, and evaluation. A quantitative survey design was used with 276 medical students as respondents. Data were collected through structured questionnaires measuring four constructs: social media use, digital literacy, counseling effectiveness, and reproductive health knowledge. Instrument testing showed that all indicators were valid, while reliability coefficients were strong for social media use (Cronbach's alpha = 0.939), digital literacy (0.923), counseling effectiveness (0.933), and reproductive health knowledge (0.926). Multiple regression analysis indicated that the three predictors simultaneously explained 51.3% of the variance in reproductive health knowledge (R = 0.716; R² = 0.513; F = 95.551; p < 0.001). In the final model, social media use showed the strongest standardized effect (β = 0.381), followed by counseling effectiveness (β = 0.346) and digital literacy (β = 0.261). The findings imply that reproductive health education in medical education should be managed as an integrated digital education strategy, combining credible social media content, critical digital literacy development, and interactive counseling. The article contributes to educational management by proposing a practical pathway for strengthening evidence-based reproductive health knowledge through digital learning governance.